2011
DOI: 10.1016/j.bbrc.2011.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of ConBr reveals molecular correlation between the carbohydrate recognition domain and endothelial NO synthase activation

Abstract: Diocleinae lectins are highly homologous in their primary structure which features metal binding sites and a carbohydrate recognition domain (CRD). Differences in the biological activity of legume lectins have been widely investigated using hemagglutination inhibition assays, isothermal titration microcalorimetry and co-crystallization with mono- and oligosaccharides. Here we report a new lectin crystal structure (ConBr) extracted from seeds of Canavalia brasiliensis, predict dimannoside binding by docking, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 26 publications
2
17
0
1
Order By: Relevance
“…These differences arise from changes in three major physicochemical parameters: binding specificity for complex carbohydrates, the pH-dependent oligomerization state (dimer-tetramer equilibrium), and the relative orientation of the carbohydrate-binding sites. The smallest CRD volume of ConBr among other Canavalia lectins has been shown to be the major reason of its lower activation of nitric oxide synthase in aortic endothelial cells [35]. In this study, the smallest CRD volume of ConBr proved to be the major reason of its high toxicity on brine shrimp.…”
Section: Resultsmentioning
confidence: 53%
“…These differences arise from changes in three major physicochemical parameters: binding specificity for complex carbohydrates, the pH-dependent oligomerization state (dimer-tetramer equilibrium), and the relative orientation of the carbohydrate-binding sites. The smallest CRD volume of ConBr among other Canavalia lectins has been shown to be the major reason of its lower activation of nitric oxide synthase in aortic endothelial cells [35]. In this study, the smallest CRD volume of ConBr proved to be the major reason of its high toxicity on brine shrimp.…”
Section: Resultsmentioning
confidence: 53%
“…It has been reported that the relative position of the carbohydrate-binding site and pH-dependent dimer-tetramer equilibrium contribute to these differences [12]; [13]; [14]. The substitution of one amino acid residue related to the carbohydrate-binding site has been held responsible for a more open carbohydrate-binding site in the lectin from Canavalia brasiliensis compared to ConA ( Canavalia ensiformis lectin) resulting in distinct activities [15]; [16]. Minor changes in the amino acid composition are also responsible for the different affinities and biological activities of the Canavalia maritima lectin [17]; [18]; [19].…”
Section: Introductionmentioning
confidence: 99%
“…According to Cavada and colleagues [34], small changes in the configuration of important amino acids from the carbohydrate recognition domain (CRD), as well as variations in pH-dependent oligomerization, may explain the differences in biological activities. Moreover, Bezerra and colleagues [35] showed that not only are the configuration and distances between residues in the CRD crucial to explain the difference in activity between Diocleinae lectins, but the volume of the CRD also plays an important role in the lectin activity. The distances between the amino acid residues involved in interactions with carbohydrates are different in ConM and ConA ( Table 2), and the CRD of ConA shows a lower volume when compared with ConM.…”
Section: Resultsmentioning
confidence: 99%
“…The distances between the amino acid residues involved in interactions with carbohydrates are different in ConM and ConA ( Table 2), and the CRD of ConA shows a lower volume when compared with ConM. The volumes for ConA PDB 1JBC and ConM PDB 2CWM are 151 and 135 Å 3 respectively, suggesting a plausible explanation for the differences in the antimicrobial actions of such lectins [35]. Although the mechanism of action of these lectins requires a better understanding, the results reported in the present article suggest that ConM acts by starting or interrupting intracellular signaling pathways that culminate with the lowest expression of genes associated with virulence and biofilm formation in S. mutans.…”
Section: Resultsmentioning
confidence: 99%